Follow-Up Clinico-Endoscopic Study among Young Patients with Peptic Ulcer Perforation: A Prospective Analysis - Aftab Rabbani, Mohammad Saud Numan, Saqib Allah Dad, Muhammad Azam, Bushra Adeel, Ayesha Masood (Pakistan Journal of Medical & Health Sciences, 2022)
Background: One of the most common difficulties in the operation fatality is perforation peritonitis. The goal of this study was to identify risk factors for peptic ulcer disease (PUD) in young patients. Materials and method: In this study, 70 patients were evaluated and clinical examinations and endoscopies were performed at 8 weeks and 6 months. Place and Duration: A population‐based cohort study was conducted at the Gastroenterology department of Sharif Medical College, Lahore for one-year duration from January 2021 to December 2021. Result: Six patients died, and 4 patients were not followed up on, out of a total of 80 patients. There were 62 men and 8 women among the remaining 70 patients. The majority of the patients were between the ages of 35 and 40. After eight weeks, 34 (50%) had no infections on endoscopy, with 34 patients (48.6%) on treatment and 1 (1.4%) not on any therapies. The residual 35 patients (50%) had active ulcers and other positive endoscopic outcomes. Six months after surgery, 56 patients (80%) had no ulcers on endoscopy, with 34 on treatment and 12 without treatment. The rest 14 had some positive endoscopic findings. The study also revealed other factors linked with peptic ulcer perforation and impacting healing in the postoperative phase. Preoperative PUD symptoms, alcohol consumption, comorbidities, chronic drug consumption (NSAIDs/steroids), smoking, postoperative treatment given and H. pylori infection were all variables. Conclusion: All patients with peptic ulcer perforation should receive H2 blockers or proton pump inhibitors as a post - operative therapies, as well as an anti-Helicobacter pylori regimen. Postoperative follow-up should include routine endoscopic examinations of these patients to detect ulcer healing.